2015
DOI: 10.3168/jds.2015-9439
|View full text |Cite
|
Sign up to set email alerts
|

Abomasal amino acid infusion in postpartum dairy cows: Effect on whole-body, splanchnic, and mammary amino acid metabolism

Abstract: Nine Holstein cows with rumen cannulas and indwelling catheters in splanchnic blood vessels were used in a generalized randomized incomplete block design with repeated measures to study the effect of increased early postpartum AA supply on splanchnic and mammary AA metabolism. At calving, cows were blocked according to parity (second and third or greater) and allocated to 2 treatments: abomasal infusion of water (CTRL; n=4) or free AA with casein profile (AA-CN; n=5) in addition to a basal diet. The AA-CN infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 43 publications
(68 reference statements)
2
38
2
Order By: Relevance
“…Although the absolute values for U:O for the group 1 AA and for total AA indicate some discrepancy on the whole, the relative differences in response to PT 5 (no effect on the total group 1 AA, increased group 2 AA) align with other studies performing mammary AA net balance under conditions of supplemental MP (Raggio et al, 2006;Haque et al, 2015). Previous mammary balance studies have produced total AA balances greater than or equal to unity (Raggio et al, 2006;Doepel and Lapierre, 2010), but some studies present values near 0.90 (Larsen et al, 2014(Larsen et al, , 2015, with values ranging from 0.83 to 0.96 within a study (Larsen et al, 2014). Furthermore, in the current study, when U:O for total AA was calculated on an N basis, the ratio increased to 0.85, 0.91, 0.93, and 0.88 for LP/LF, HP/ LF, LP/HF, and HP/HF, respectively.…”
Section: Aa Utilization With Energy From Proteinsupporting
confidence: 64%
“…Although the absolute values for U:O for the group 1 AA and for total AA indicate some discrepancy on the whole, the relative differences in response to PT 5 (no effect on the total group 1 AA, increased group 2 AA) align with other studies performing mammary AA net balance under conditions of supplemental MP (Raggio et al, 2006;Haque et al, 2015). Previous mammary balance studies have produced total AA balances greater than or equal to unity (Raggio et al, 2006;Doepel and Lapierre, 2010), but some studies present values near 0.90 (Larsen et al, 2014(Larsen et al, , 2015, with values ranging from 0.83 to 0.96 within a study (Larsen et al, 2014). Furthermore, in the current study, when U:O for total AA was calculated on an N basis, the ratio increased to 0.85, 0.91, 0.93, and 0.88 for LP/LF, HP/ LF, LP/HF, and HP/HF, respectively.…”
Section: Aa Utilization With Energy From Proteinsupporting
confidence: 64%
“…Infusions of casein in the abomasum or intestine, increases the milk production (Chalupa and Sniffen, 1991;Larsen et al, 2015;Hills et al, 2015). However, in Brazil according to Santos and Greco (2007) from 127 compared 88 experiments with cows in milk production, where the soybean meal was replaced partly or wholly by RUP rich sources, have concluded that only 17% of cows showed an increase in milk production due to the processing of soybean meal.…”
Section: Effect Of Protein Sources On Milk Production and Compositionmentioning
confidence: 99%
“…In this regard, degradation of BCAA (transamination or oxidative decarboxylation of 3557 the transamination products) has been studied in different tissues of ruminants, including the digestive tract (Pell et al, 1986;MacRae et al, 1997), liver , muscle (Pell et al, 1986;Bequette et al, 2002), and MG (Bequette et al, 1996a,b;Thivierge et al, 2002). However, previously published data on BCAA net fluxes and isotopic tracer studies in dairy cows have shown that, quantitatively, hepatic removal of BCAA (and their metabolites) is limited, as is their oxidation Raggio et al, 2004;Larsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%